Cold Agglutinin Disease Secondary to Multiple Myeloma in a Psoriatic Patient (Journal of Medicine, 2014)
Cold agglutinin disease (CAD) is a chronic compensated hemolytic anemia. We report a case of cold agglutinin disease secondary to multiple myeloma (MM) in a patient of erythrodermic psoriasis. The patient presented with acral cyanosis, progressive weakness and generalized desquamating scaly lesions. After confirming the diagnosis (80-90% plasma cells in bone marrow, M- spike in serum protein electrophoresis, G-ë restriction pattern in immune electrophoresis) he was given chemotherapy with CTD (cyclophosphamide, thalidomide and dexamethasone) protocol. His clinical symptoms improved and he has now completed 4 cycles of chemotherapy. The interim follow up showed achievement of PR (partial response).DOI: http://dx.doi.org/10.3329/jom.v15i2.20688 J MEDICINE 2014; 15 : 141-143